1979
DOI: 10.1001/jama.1979.03300100038019
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia After Thoracentesis

Abstract: Hypoxemia was observed at 20 minutes and two hours postprocedure in 15 patients who had a thoracentesis. The hypoxemia resolved after 24 hours. No effect on pH, PaCO2, or bicarbonate ion was observed. The degree of hypoxemia was correlated directly with the volume of fluid removed. Oxygen therapy was found to reverse this effect. Hypoxemia that follows thoracentesis may be caused by several factors, the most important being frank pulmonary edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Another study3 demonstrated that thoracocentesis is accompanied by a lowering of PaO 2 , in accordance with Karetzky and colleagues,4 supporting the notion that thoracocentesis results in significant hypoxaemia due to disequilibrium of the ventilation–perfusion relationship. However, Light and colleagues5 reported improvement in lung volumes after removal of fluid.…”
Section: Introductionsupporting
confidence: 71%
“…Another study3 demonstrated that thoracocentesis is accompanied by a lowering of PaO 2 , in accordance with Karetzky and colleagues,4 supporting the notion that thoracocentesis results in significant hypoxaemia due to disequilibrium of the ventilation–perfusion relationship. However, Light and colleagues5 reported improvement in lung volumes after removal of fluid.…”
Section: Introductionsupporting
confidence: 71%
“…The length of time the effusion has been present and the volume aspirated may also affect the response. There may be increased interstitial capillary permeability 18 or an alteration of surfactant synthesis in the compressed lung that increases with time and volume 19 . Some studies have demonstrated significant improvement after removal of as little as 800 mL pleural fluid 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in gas exchange are more consistently found at 24 h [5,9], rather than immediately [7,1012] after thoracentesis. Hypoxemia has been shown to worsen up to 2 h after thoracentesis [13]. These observations have been attributed to re-expansion pulmonary edema or delayed pulmonary re-expansion.…”
Section: Pathophysiological Effects Of a Pleural Effusionmentioning
confidence: 99%